Functional outcome of volar locking plate for unstable distal radius fractures - Sharma, Bishnu Dev; Prajapati, Akesh; Regmi, Ananda Prasad; Sitaula, Jyoti; Shrestha, Sujit; Panta, Pujan; Rijal, Sanjeeb (Journal of Chitwan Medical College, 2018)
Introduction: Distal radius fractures are the most common fractures in elderly. Unstable fractures are best managed surgically and the results of volar locking plates have been promising. The purpose of this study is to determine the functional outcome of volar locking plates in the treatment of unstable distal radius fractures. Methods: Forty-five patients with 46 unstable distal radius fractures were enrolled for this study, conducted at Chitwan Medical College from September 2016 to April 2017. All patients were treated with a 3.5mm titanium volar locking plate and followed-up for a minimum of one year. The assessment was done using radiological evaluation and Cooney modification of the Green and O’Brien scoring system. Results: Twenty-three men and 22 women with age ranging from 15-75 years (mean 43.22 years) were followed-up for an average of 16.53 months. There were 17 type A fractures (5 A2, 12 A3), 11 type B fractures (3 B1, 1 B2, 7 B3), and 18 type C fractures (4 C1, 12 C2, 2 C3) (AO classification). The mean time for union was 7.96 weeks. Functional outcome using modified Green and O’Brien Score was 20 excellent, 15 good, 7 fair and 4 poor results (76.1% good to excellent results). The overall complication rate was 15.22%. Conclusion: Volar locking plates provide adequate fixation for unstable distal radius fractures with minimal loss of reduction and satisfactory functional outcome.